The Differences in Effect Between Back Massage Therapy and Gym Ball on Back Pain in Pregnant Women Third trimester - Hasnia, Hasnia; Dinengsih, Sri (Universitas Islam Lamongan, 2023)
Pregnancy is an event that occurs in a woman, starting from the fertilization process (conception) until the birth of the baby. This process causes physical, mental and social changes which are influenced by several physical, psychological, environmental, socio-cultural and economic factors. The discomfort that pregnant women often experience, especially in the third trimester of pregnancy, is back pain. The objective of the research are knowing perbedaan providing back massage and gym ball therapy for back pain in third trimester pregnant women at TPMB